Sustainable cooperation in international trade: A quantitative analysis - MEI, Yuan (Institutional Knowledge at Singapore Management University, 2020)
How does the presence of multilateral institutions affect the sustainability of trade-policy cooperation? Do free-trade agreements make multilateral cooperation less sustainable? Will countries be more likely to deviate from negotiated tariffs when more trade liberalization realizes in the future? These questions have been studied in theory literature using models that feature repeated games, but have yet to be quantitatively analyzed. In this paper, I propose a methodology to quantitatively characterize the equilibrium strategies on tariffs of various nations in a widely used repeated-game framework. I then apply this methodology to address these questions from a quantitative perspective. The numerical results computed from a reasonably comprehensive general equilibrium trade model corroborate previous analysis derived theoretically from simpler trade models. However, only free-trade agreements appear to influence the sustainability of trade-policy cooperation with quantitative significance.